2018
DOI: 10.1051/matecconf/201817804003
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the geometric change of plastic articles made by polyamide

Abstract: The following paper includes an investigation of the geometric variation of plastic workpieces in a simulated environment of normal climate by 21° / 50% relative humidity. In the industrial manufacturing, the daily quality checks are required to determine, if the plastic workpieces can be released. Due to the humidity or water absorption, the plastic workpiece grows so far that the dimensional accuracy is not given. In this investigation, the results of 12 weeks are determined and presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…One of the main drawbacks of 3D printed materials is their tendency to absorb humidity, causing dimensional and geometric instability. Aclan et al [17] confirmed this in their study. Clavería et al [18] explored the impact of environmental conditions on dimensional stability for injected parts in Polyamide 6 (PA6) and Polyamide 66 (PA66), finding an average dimension variation of 12% for PA6 and 3% for PA66.…”
Section: Introductionsupporting
confidence: 62%
“…One of the main drawbacks of 3D printed materials is their tendency to absorb humidity, causing dimensional and geometric instability. Aclan et al [17] confirmed this in their study. Clavería et al [18] explored the impact of environmental conditions on dimensional stability for injected parts in Polyamide 6 (PA6) and Polyamide 66 (PA66), finding an average dimension variation of 12% for PA6 and 3% for PA66.…”
Section: Introductionsupporting
confidence: 62%